Hakikat Fitrah Manusia dalam Islam - Suriadi Samsuri (IAIN PAREPARE, 2020)
This article discusses the nature of human nature in Islam. This study focuses on the verses of the Koran surah al-Rum ayart 30. The concept of fitrah in al-Qur'an surah al-R ayatm verse 30 that humans are required to remain in nature as servants of God (abdullah), as the caliph of God (kolifatullah). To determine this nature requires an educational effort that is human in nature through humanitarian education, namely education that humanizes humans. From birth humans have brought about fitrah (potential), a tendency to be good or bad, to be good or bad. It depends on human interaction with the surrounding environment. Therefore, in an effort to preserve and develop a better fitrah, the educational process is needed with the aim that the fitrah remains in the provisions of God as desired in surah al-Rûm verse 30.